PENGARUH MEDIA PEMBELAJARAN INTERAKTIF GAME EDUKASI WORDWALL TERHADAP MINAT BELAJAR SISWA PADA PEMBELAJARAN EKONOMI - Faikotun Nafiah; Putri Ulfa Kamalia (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
The low interest in learning Economics among students due to the dominance of conventional worksheets demands innovation in more interactive technology-based learning media. This study aims to test the effect of using the Wordwall educational game on the learning interest of class XI students of SMAN 22 Surabaya. Using a quasi-experimental method with a nonequivalent control group design, this study involved class XI-6 as the experimental group and XI-7 as the control through a saturated sampling technique. The research stages included a pretest, treatment using the Random Wheel and Open the Box features, and a posttest. Quantitative data were analyzed using the Independent Sample T-Test and N-Gain tests. The research findings showed a significant effect of Wordwall on learning interest with a significance value of 0.000 less than 0.05. The learning interest score of the experimental class increased from 72.09% to 84.63% or in the high category, surpassing the control class which only reached 75.64%. The N-Gain test results of the experimental group were 42.18%, which is in the medium category and proved to be much more effective than the control group at 36.79%. Supported by 92.19% observation results, this media was able to create a challenging and participatory learning environment for the students studied. The main conclusion confirms that the integration of the Wordwall educational game effectively optimizes student interest through hands-on learning experiences in accordance with constructivist principles. This innovation serves as a strategic guide for educators in utilizing digital technology to transform the quality of economics learning.